The effect of memorizing the Quran on students' mathematical logical intelligence - asliyah, nur; Ananda, Rusydi (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this research is to determine the magnitude of the impact of memorizing the Quran on the logical-mathematical intelligence of students at the Private MTs Al-Jamaiyah Medan in the 2021/2022 academic year. This research is research that uses a quantitative approach and a kind of ex-post research. In this research, there are two variables, the independent variable is the memorization of the Quran and the dependent variable is mathematical logical intelligence. The population in this research amounted to 105 students. The sampling technique used simple random sampling. The data analysis method used was simple linear regression analysis. Guided by the results of data analysis, it was found that there is an effect of memorizing the Quran on mathematical logical intelligence. The value of determination shows that 74.1% of memorizing the Quran affects students' logical-mathematical intelligence and the remaining 25.9% is influenced by other factors